Reinterpreting Talik Talak in Indonesia: Harmonizing Fiqh and the Compilation of Islamic Law in Indonesia - Ach. Ainul Yaqin; Fadil SJ; Zaenul Mahmudi (At-Tafkir, 2025)
This study addresses the conceptual tension between classical fiqh and the Indonesian Compilation of Islamic Law (Kompilasi Hukum Islam or KHI) in regulating ta‘lik talak, particularly in relation to the protection of women’s rights and marital justice. It aims to reinterpret ta‘lik talak through a harmonization framework that integrates classical Islamic jurisprudence with contemporary statutory regulation in Indonesia. Employing a normative comparative method, this research is based on a comprehensive literature review of primary legal sources, including the Quran, hadith, classical fiqh texts, and the KHI, supported by relevant secondary legal materials. The findings reveal that classical fiqh conceptualizes ta‘lik talak as a flexible and consensual mechanism grounded in private agreement, whereby divorce takes effect automatically upon the fulfillment of stipulated conditions. In contrast, the KHI institutionalizes ta‘lik talak within a formal legal framework that requires judicial intervention through religious courts to activate its legal consequences, thereby prioritizing women’s legal protection and procedural certainty. The harmonization of these two approaches illustrates the transformation of Islamic family law from a predominantly moral individual paradigm toward a legal formal system, while maintaining the substantive objectives of Shari‘ah in response to Indonesia’s socio legal context. This study contributes to the development of Islamic family law by affirming ta‘lik talak as a dual legal instrument that is both normative religious and statutory, capable of enhancing women’s rights protection, safeguarding marital stability, and operationalizing the principles of maqasid al shari‘ah within Indonesia’s positive legal order.